Parents' and families' experiences of palliative and end-of-life neonatal care in neonatal settings: a systematic review protocol. (November 2016) - Foster, Jann; Kain, Victoria; Patterson, Tiffany
Abstract : Review question/objective: The overall objective of this systematic review is to identify, critically appraise and synthesize the parents' and families' experiences of palliative and end-of-life neonatal care at facilities/services globally. The specific review question is: what are parents' and families' experiences of palliative and end-of-life neonatal care?